Lessons learnt on recruitment and fieldwork from a pilot European human biomonitoring survey - Fiddicke, Ulrike; Becker, Kerstin; Schwedler, Gerda; Seiwert, Margarete; Joas, Reinhard; Joas, Anke; Biot, Pierre; Aerts, Dominique; Casteleyn, Ludwine; Dumez, Birgit; Castaño, Argelia; Esteban, Marta; et al. (Environmental research, 2015)
Within the European Environment and Health Action Plan an initiative to establish a coherent human biomonitoring approach in Europe was started. The project COPHES (COnsortium to Perform Human biomonitoring on a European Scale ) developed recommendations for a harmonized conduct of a human biomonitoring (HBM) survey which came into action as the pilot study DEMOCOPHES (DEMOnstration of a study to COordinate and Perform Human biomonitoring on a European Scale). Seventeen European countries conducted a survey with harmonized instruments for, inter alia, recruitment, fieldwork and sampling, in autumn/winter 2011/2012. Based on the countries' experiences of conducting the pilot study, following lessons learnt were compiled: the harmonized fieldwork instruments (basic questionnaire, urine and hair sampling) turned out to be very valuable for future HBM surveys on the European scale. A school approach was favoured by most of the countries to recruit school-aged children according to the established guidelines and country specific experiences. To avoid a low participation rate, intensive communication with the involved institutions and possible participants proved to be necessary. The communication material should also include information on exclusion criteria and offered incentives. Telephone contact to the participants the day before fieldwork during the survey can prevent the forgetting of appointments and first morning urine samples. To achieve comparable results on the European scale, training of interviewers in all issues of recruitment, fieldwork and sampling through information material and training sessions is crucial. A survey involving many European countries needs time for preparation and conduct. Materials for quality control prepared for all steps of recruitment, fieldwork and sampling proved to be important to warrant reliable results.
Keywords: International Cooperation; Environmental Monitoring; DEMO/COPHES; Human biomonitoring; směrnice jako téma; průzkumy a dotazníky; Research Design; Lessons learned; Informed Consent; Sampling Studies; Humans; Electronic Data Processing; Europe; Interprofessional Relations; Program Development; Quality Control; Guidelines as Topic; Environmental Health; environmentální zdraví; vzorkové studie; informovaný souhlas pacienta; monitorování životního prostředí; Health Personnel; Pilot Projects; Evropa; lidé; rozvoj plánování; výzkumný projekt; Fieldwork; řízení kvality; Surveys and Questionnaires; pilotní projekty; automatizované zpracování dat; Recruitment; mezinárodní spolupráce; interprofesionální vztahy; zdravotnický personál